1998
DOI: 10.1021/jp980017s
|View full text |Cite
|
Sign up to set email alerts
|

Refinement and Parametrization of COSMO-RS

Abstract: The continuum solvation model COSMO and its extension beyond the dielectric approximation (COSMO-RS) have been carefully parametrized in order to optimally reproduce 642 data points for a variety of properties, i.e., ∆G of hydration, vapor pressure, and the partition coefficients for octanol/water, benzene/water, hexane/ water, and diethyl ether/water. Two hundred seventeen small to medium sized neutral molecules, covering most of the chemical functionality of the elements H, C, N, O, and Cl, have been conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
1,763
0
6

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 1,748 publications
(1,788 citation statements)
references
References 24 publications
19
1,763
0
6
Order By: Relevance
“…Indeed, this is in quite good agreement with the fact that the polarisation charge densities in a non-polar solvent typically are by a factor of 0.8 smaller than in a conductor, due to the almost complete lack of electronic back-polarisation in non-polar solvents. 36 Since we are using as descriptors s values calculated in a conductor environment here, and since this reduction applies to the donor and acceptor, we would expect a reduction of the slope of DH o HB , vs. s by a factor of B0.8 2 = 64%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, this is in quite good agreement with the fact that the polarisation charge densities in a non-polar solvent typically are by a factor of 0.8 smaller than in a conductor, due to the almost complete lack of electronic back-polarisation in non-polar solvents. 36 Since we are using as descriptors s values calculated in a conductor environment here, and since this reduction applies to the donor and acceptor, we would expect a reduction of the slope of DH o HB , vs. s by a factor of B0.8 2 = 64%.…”
Section: Resultsmentioning
confidence: 99%
“…The suitability of the polarisation charge density for the quantification of intermolecular interaction has been demonstrated by Klamt in his COSMO-RS solvation model. [20][21][22] For those not familiar with the concept of COSMO, a more detailed description and discussion of the polarisation charge density s is given in appendix SI1 in the ESI. † The study on the quantum chemically calculated HB complexes confirmed the bilinear s-dependence of HB bond energies assumed within the COSMO-RS.…”
Section: Introductionmentioning
confidence: 99%
“…These calculations were performed with default values for all parameters (implying a water-like probe molecule) and a dielectric constant of 80. For the generation of the cavity, we used the optimised COSMO radii in Turbomole (1.30, 2.00, 1.72, and 2.05 Å for H, C, O, and Cl, respectively) [59].…”
Section: Dft-d Calculationsmentioning
confidence: 99%
“…The total number of surface segments in a molecule is i i e f f n A a = , where 2 eff a a r ν = π is the standard segment surface area and av r is the averaging radius, one of the adjustable parameters studied in this paper. It is usual in the literature to find two values for the averaging radius (Grensemann & Gmehling, 2005;Klamt et al, 1998), one used to determine the surface area eff (r ) and another for the σ-profile averaging procedure av (r ) . In this work, av r will be used in both calculations.…”
Section: Brazilian Journal Of Chemical Engineeringmentioning
confidence: 99%